Environmental Barriers to Networking - William Spitzer (Journal of Research in Rural Education, 1993)
The two preceding articles highlight some of the potential benefits that telecommunication can provide to teachers and students. Here, I examine what it takes to create and sustain a learning environment that includes telecommunication, and what barriers exist for both new and experienced users.